Perancangan Desain Meja Belajar Dinding Minimalis dengan Menggunakan Metode Quality Function Deployment - Fathoni, Doni Okta Nur; Agustina, Arisa; Komariah, Ainur (Universitas Al Azhar Indonesia, 2025)
Furniture is one of the main needs of every home. Furniture designs that are currently trending are minimalist designs, namely designs that prioritize the main function and comfort of the user. One type of furniture that many consumers need is a study table. There are many study table designs available, but there are consumer needs that have not been met by the available product designs. The aim of this research is to design a minimalist wall study table. A study table attached to the wall will be functional and save space. This is in accordance with the minimalist concept applied. The method used is Quality Function Deployment (QFD). This QFD method involves consumers from the early design stages so that the design results will be in accordance with what consumers need. Consumer needs are then linked to the corresponding technical characteristics. The technical characteristics of a study table with the highest value are the main priority in design. The survey results using the QFD method show that the technical characteristics with the highest scores are (a) selection of durable basic materials (score 5.96); (b) ergonomic design (score 5.95) and additional components (score 5.37). The results of comparing with competitor products show that the product developed is superior.Keywords – furniture, minimalist, wall study table, QFD